(How) ChatGPT-Artificial Intelligence Thinks It Can Help/Harm Physiatry - Jačisko, Jakub; Veselý, Viktor; Chang, Ke-Vin; Özçakar, Levent (American journal of physical medicine & rehabilitation, 2024)
ChatGPT is a chatbot that is based on the generative pretrained transformer architecture as an artificial inteligence-based large language model. Its widespread use in healthcare practice, research, and education seems to be (increasingly) inevitable. Also considering the relevant limitations regarding privacy, ethics, bias, legal, and validity, in this article, its use as a supplement (for sure not as a substitute for physicians) is discussed in light of the recent literature. Particularly, the "opinion" of ChatGPT about how it can help/harm physiatry is exemplified.
Keywords: jazyk (prostředek komunikace); Dietary Supplements; Physical and Rehabilitation Medicine; Artificial Intelligence; Language; umělá inteligence; stupeň vzdělání; rehabilitační lékařství; Humans; lidé; Educational Status; potravní doplňky